Policy Analysis of Retention of Physicians in Deprived Areas in Iran Using a Framework of Policy Analysis Triangle - Mohammad Alimoradnori; Asgar Aghaei Hashjin; Badrye Karami (Shahid Sadoughi University of Medical Sciences, 2023)
Background: The retention of physicians' policy is recommended by the World Health Organization (WHO) to achieve the goals of the health system and justice in access to health services. The aim of this study was policy analysis of retention of physicians in deprived areas and providing some recommendations for improvement of this plan. Methods: This was a qualitative study regarding policy which used Walt and Gilson's triangle framework and Kingdon's multiple streams. Data were collected using a deep semi-structured interview with 30 participants and a review of upstream laws and regulations. After that, all the interviews were recorded, transcribed, and reviewed. Then, data were analyzed through MAXQDA/12 and content analysis. Results: The findings of this study were categorized according to the policy context, content, and process, and actors who played a significant role in designing and implementing this policy. Conclusion: The policy of retaining physicians in rural areas requires the support of the majority of the country's political and health authorities, and providing infrastructure for health providers. This policy not only increases the quality of services, but also is effective in increasing the patients' access to healthcare services in deprived areas.